Patient-reported vision impairment in low luminance predicts multiple falls - Terheyden, Jan H.; Gerhards, Johanna; Ost, Reglind A. D.; Wintergerst, Maximilian W. M.; Holz, Frank G.; Finger, Robert P. (BMC geriatrics, 2023)
Background: Visual impairment is an independent risk factor for falling. Whether this extends to patient-reported visual difficulties has not been assessed to date. We have evaluated whether patient-reported visual difficulties in low-contrast and low luminance situations are a risk factor for falls and concerns about falling. Methods: Baseline assessments in outpatients with varying degrees of visual impairment aged ≥ 60 years included the Vision Impairment in Low Luminance (VILL) questionnaire and socio-demographic data; prospective follow-up assessments included falls over 12 months, the Falls Efficacy Scale (FES-I) and the VILL. The VILL was scored using Rasch models, and the FES-I was categorized following published guidelines. Associations were investigated using logistic regression analysis, controlling for age, visual acuity and known risk factors of falling. Results: We included 112 participants (74 women, mean age 70 ± 7 years). Twenty-seven participants recalled any falls and eleven recalled multiple falls at follow-up. Higher VILL reading subscale and mobility subscale scores at baseline were significantly associated with reporting less multiple falls at follow-up (OR 0.559 [0.333–0.936], p = 0.027 and OR 0.595 [0.377–0.940], p = 0.026). VILL scores were significantly associated with concerns about falling (high versus low: p ≤ 0.004, reading, mobility and emotional subscales; high versus moderate: p = 0.004, emotional subscale). Conclusions: Patient-reported visual difficulties under low illumination and in low-contrast conditions are predictive of multiple falls in the future, have an additional predictive value over established risk scores, and are associated with concerns to fall. Current fall risk assessments may benefit from the inclusion of such assessments, e.g. the VILL questionnaire.
Veröffentlicht: 21. September 2023
Gesehen am 20.11.2023